Improvement of Managerial Communications in Sports Clubs - Gheorghe JINGA; Adrian IACOBINI (Revista de Management Comparat International)
Organizational decisions are highly dependent on the quality and quantity of information being exchanged. Poor or incomplete information can negatively impact a manager's ability to successfully make decisions. Due to the nature of the work in sports clubs the teachers perform (activity in sports stadiums, travel for competitions, etc.), usually they are not in the same building with their management. This fact requires modifying the communication of information through one accessible. As techniques and technology have invaded our lives the most optimal way is the communication of information throw technical devices. Nowadays almost everyone has a cell phone, which he carries all the time. Thus, communication using the smart phone is effective, fast and safe.